Maximum principle for problem of circuit optimisation. Issue 9 (4th April 2016) - Zemliak, A.
Abstract : The solution of a problem of circuit optimisation for minimum possible CPU time is obtained on the basis of the maximum principle of Pontryagin. It is shown that the effect of acceleration of the optimisation process that was studied earlier coincides with the solution obtained on the basis of the maximum principle. This is a theoretical justification of the effect of acceleration. On the other hand, the maximum principle can be a basis for development of optimisation algorithm for electronic circuits with the minimum expenses of CPU time.